Efisiensi Pengelolaan Waktu Dalam Mengatasi Kesulitan Belajar Siswa Pada Pembelajaraan Aqidah Dan Akhlak - Atiqah Rafidah Ekadina; Herkolis Eko Pronomo; Yusup Kholid Akbar (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This research examines the efficiency of time management in overcoming students' learning difficulties in Aqidah and Akhlak (Islamic Theology and Ethics) learning in seventh grade at Madrasah Tsanawiyah Negeri 1 Bengkulu. The phenomenon of students' inability to manage study time effectively underscores the urgency of this research, considering its implications for academic performance and internalisation of moral-religious values. This qualitative research with a narrative approach involved 15 respondents, consisting of seventh-grade students, Aqidah Akhlak subject teachers, and homeroom teachers. Data collection techniques included in-depth interviews, participatory observation, and documentation study, with data analysis through the stages of reduction, presentation, and verification based on the Miles and Huberman model. Source and method triangulation were implemented to ensure data credibility. The research findings identified that students' learning difficulties are influenced by internal factors such as emotional instability and sensory disturbances, as well as external factors including family disharmony, economic limitations, negative social environment, and inadequate learning facilities. Analysis of time management efficiency revealed deficiencies in long-term goal formulation, systematic planning implementation, and the proportion balance between academic and recreational activities. The research findings contribute to the development of an integrated pedagogical intervention model that accommodates time management skills in the Aqidah Akhlak curriculum. The practical implications of the research point to the urgency of collaboration among educational tricenters to create an ecosystem that supports the optimisation of students' time management skills, thereby overcoming learning difficulties and enhancing understanding and appreciation of religious values